Time Course of Corticospinal Excitability and Intracortical Inhibition Just before Muscle Relaxation - Suzuki, Tomotaka; Sugawara, Kenichi; Ogahara, Kakuya; Higashi, Toshio (Frontiers in Human Neuroscience, 2016)
Using transcranial magnetic stimulation (TMS), we investigated how short-interval intracortical inhibition (SICI) was involved with transient motor cortex excitability changes observed just before the transition from muscle contraction to muscle relaxation. Ten healthy participants performed a simultaneous relaxation task of the ipsilateral finger and foot, relaxing from 10% of their maximal voluntary contraction force after the go signal. In the simple reaction time paradigm, single or paired TMS pulses were randomly delivered after the go signal, and motor evoked potentials were recorded from the right first dorsal interosseous muscle. We analyzed the time course prior to the estimated relaxation reaction time, defined here as the onset of voluntary relaxation. SICI decreased in the 80–100 ms before relaxation reaction time, and motor evoked potentials were significantly greater in amplitude in the 60–80 ms period before relaxation reaction time than in the other intervals in single-pulse trials. TMS pulses did not effectively increase relaxation reaction time. These results show that cortical excitability in the early stage, before muscle relaxation, plays an important role in muscle relaxation control. SICI circuits may vary between decreased and increased activation to continuously maintain muscle relaxation during or after a relaxation response. With regard to motor cortex excitability dynamics, we suggest that SICI also dynamically changes throughout the muscle relaxation process.